2009
DOI: 10.1016/j.mimet.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome amplification of the rust Puccinia striiformis f. sp. tritici from single spores

Abstract: Rust fungi are obligate parasites and cannot be routinely cultured to obtain sufficient biomass for DNA extractions. Multiple displacement amplification (MDA) was demonstrated in this study for whole genome amplification from single spores of the rust fungus, Puccinia striiformis. The genomic DNA coverage and fidelity of this method was evaluated by PCR amplification and sequencing of two genetic markers: portions of the multi-copy nuclear ribosomal DNA internal transcribed spacer region (ITS) and the single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It has been observed that a quota of GBM CD31+ endothelial cells shares with tumors cells chromosomal aberrations [140] and that a quota of GBM CD105+ endothelial cells harbours the same somatic mutations identified within tumor cells, such as amplification of EGFR and chromosome 7 [141]. In a GBM model, it was demonstrated that the tumor-derived endothelial cells originated from TICs [138].…”
Section: Perivascular Niches (Pvn) Relationship Between Npcs/gscs Anmentioning
confidence: 99%
“…It has been observed that a quota of GBM CD31+ endothelial cells shares with tumors cells chromosomal aberrations [140] and that a quota of GBM CD105+ endothelial cells harbours the same somatic mutations identified within tumor cells, such as amplification of EGFR and chromosome 7 [141]. In a GBM model, it was demonstrated that the tumor-derived endothelial cells originated from TICs [138].…”
Section: Perivascular Niches (Pvn) Relationship Between Npcs/gscs Anmentioning
confidence: 99%
“…MDA was evaluated for amplification of genomic DNA from single urediospores in a previous study ). Wang et al (2009) tested the fidelity of the MDA process by sequencing of two genetic markers: portions of the multicopy nuclear ribosomal DNA internal transcribed spacer (rDNA-ITS) region and the single-copy β-tubulin gene and found that sequences of these two markers were highly consistent between DNA synthesized via MDA and DNA extracted via CTAB method. However, whether this method can amplify other regions of the pathogen genome equally well remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…The MDA of single cells for preimplantation genetic diagnosis was successfully used for analyzing Duchenne muscular dystrophy (Ren et al, 2009). MDA of gDNA from single spores of a rust fungus Puccinia striiformis can be used in molecular genetic analysis of the wheat yellow rust fungus (Wang et al, 2009). Moreover, MDA can convert complex mixtures of DNA fragments to long linear and circular concatamers, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%